DESAIN LEMARI PENYIMPANAN BUKU UNTUK MENUNJANG PROGRAM LITERASI SMAN 6 SAMARINDA - H, Roni; Wulandari, Septiana Rizky (Indonesian Society of Applied Science, 2018)
ABSTRACTThe design and development of this product is a part of the abstract changes that exist in the business world. In a classroom measuring 9m x 8m that will be used to place a book storage cabinet for this activity does not take many places. Book storage cabinets like these require to place books according to the size of the shelves that are already designed using A4 paper rules. Designing a Book Storage Cabinet product using the Adiwiyata concept which means an environmental program by taking colors that have a natural impression, and cool and using a modern minimalist design style to fit the classroom that is not too spacious. With the design methods that have been done include: Design stages, Preliminery design, Problem formulation, Literature review, Analysis and design specifications, Design specifications, Design develoment, Final designs and prototypes. So that a book storage cabinet design has been produced that has a modern minimalist design style.Keywords: Cupboard, Storage, Books